A rare tumor at a rare location: facial nerve schwannoma - Doloi, Pankaj Kumar; Sharma, Mitesh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Schwannomas are benign, slow-growing tumours arising from Schwann cells within the nerve sheath with no gender preferance. We present a 29-year-old female patient attending ENT OPD at St. Stephens Hospital, New Delhi with complain of left-sided infrauricular, painless swelling for 3 months which was insidious in onset, and progressive in nature. NCCT neck showed enlarged left parotid gland and USG showed a cystic lesion in left parotid tissue. Superficial parotidectomy was planned according to the above findings and the sample was sent for histopathological examination. IHC markers were applied and features were suggestive of benign peripheral nerve sheath tumor favoring schwannoma. Schwannomas can sometimes mimic as enlarged parotid tumour in its rarest presentation. This case report is in view of evaluating parotid mass in a broader aspect and manage accordingly.